Lean Management Practices’ Effects on Brazilian Firms: A Quantitative and Qualitative Analysis - Sousa, Filipe Lage de; Canêdo-Pinheiro, Mauricio; Cabral, Bernardo Pereira; Sousa Ferreira, Glaucia Estefânia de (Journal of Contemporary Research in Business, Economics and Finance, 2021)
One of the key drivers for a firm’s productivity growth is management. One lean management practice considered cost-effective is Kaizen. Originally from Japan, the Kaizen basic concept is continuous improvement with the involvement of the full workforce. Using a firm-level dataset from Brazil’s innovation and manufacturing surveys, this paper evaluates quantitatively whether Kaizen has impacted the performance of domestic firms. Our initial results suggest a productivity premium on Kaizen adopters, yet when it materializes is not detectable in the short term. Moreover, the impact on innovation is observable after Kaizen implementation. Understanding these outcomes with a qualitative approach, our analysis highlights the importance of Kaizen on innovation, especially by improving worker’s time at the production line as well as the long-term vision of Kaizen on productivity. In summary, Kaizen is not a magic wand that improves firms’ performance in a wide array of indicators yet it may boost innovation outcomes in the short term aiming to improve productivity in the long term if it is implemented carefully and persistently, as established by its basic principles.